Sistem Kontrol Irigasi Otomatis Nirkabel - - Wiranto; Budi Indra Setiawan; Satyanto Krido Saptomo (Balai Teknik Irigasi, 2014)
Irrigation water provides on agricultural land should be used optimally, that automatic irrigation system that is able to provide crop water with the expected conditions are needed. For wide area the automatic irrigation system a use wireless sensor network system (WSN). The advantages of this system such as easy data download and the device is easy to install so the user will convenient to monitoring the entire irrigated area. In this research, XBee / XBee pro was used as wireless system devices with radio communication system and GSM modem device for SMS communication system. The objective of this research is to improve the efficiency of irrigation systems for wireless control. The benefits of this study is to provide an alternative automatic irrigation system for the region with limited water availability because the system is able to regulate irrigation water allocation according to crop needs (efficiency of irrigation water use).